How Far Goods Travel: Global Transport and Supply Chains from 1965-2020 - Sharat Ganapati; Woan Foong Wong (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper considers the evolution of global transportation usage over the past half century and its implications for supply chains. Transportation usage per unit of real output has more than doubled as costs decreased by a third. Participation of emerging economies in world trade and longer-distance trade between countries contribute to this usage increase, thereby encouraging longer supply chains. We discuss technological advances over this period, and their interactions with endogenous responses from transportation costs and supply chain linkages. Supply chains involving more countries and longer distances are reflective of reliable and efficient transportation, but are also more exposed to disruptions, highlighting the importance of considering the interconnectedness of transportation and supply chains in policymaking and future work.
Keywords: F01; F15; R4; R40; 330; Internationaler Güterverkehr; Verkehrsaufkommen; Außenhandel; Geographische Entfernung; Lieferkette; Globalisierung; Transportkosten; Welt